PERANCANGAN BOOKLET SEBAGAI MEDIA PROMOSI OBJEK WISATA KABUPATEN PESISIR SELATAN - FITRA DEWI, Drs. Suib Awrus, M.Pd., Drs. Syafei, M. Ag. (Universitas Negeri Padang, 2016)
West Sumatera is well known with its natural beauty. One of the natural beauties in West Sumatera is the tourism attraction of Pesisir Selatan Regency. The tourism attractions in Pesisir Selatan Regency are; Carocok Beach, Langkisau Hill, Timbulun Waterfall, Bayang Sani Waterfall, Akar Bridge, Mandeh Tourism area and Cubadak Island. Yet, not all tourism attractions are known to the society, because all this time the promotion media used was only small billboard, banner, and electronic media such as television commercials, audio visual, etc.The objectives of the design were: 1) to promote tourism destination of Pesisir Selatan Regency which has enchantment and natural beauty in order to be acknowledge by the society in larger scope, 2) to make the tourism attraction of Pesisir Selatan regency to be the alternative choices for society and for domestic and foreign tourist, and 3) to encourage the proclivity of Tourism Department of Pesisir Selatan Regency to be more observant and make its tourism destinations better than before.The method of data collection in order to start the designing process could be divided into two; a) primary data, which was the visual data of the tourism attraction in Pesisir Selatan Regency, and b) secondary data, which was the review of related literature that was taken from the library, books, and internet. The data analysis used was SWOT analysis. This method was needed to strengthen and perfect the design.The product of the design was A5 booklet and it displays the images of tourism attractions in Pesisir Selatan Regency. The supporting media of the tourism attraction in Pesisir Selatan Regency were badge, sticker, mug, shirt, clock, key chain, and calendar. May the promotion of tourism attraction in Pesisir Selatan Regency by using the booklet media work well and draw the domestic and foreign tourists to come.